2012
DOI: 10.3762/bjoc.8.173
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cyclodextrin on the solubility of a classically prepared 2-vinylcyclopropane macromonomer in aqueous solution

Abstract: SummaryA macromonomer 5 consisting of a polymerizable vinylcyclopropane end group and a poly(N-isopropylacrylamide) (poly(NiPAAm)) chain was obtained from amidation of 1-ethoxycarbonyl-2-vinylcyclopropane-1-carboxylic acid (4) with an amino-terminated poly(NiPAAm) 3 as an example. This macromonomer 5 showed an LCST effect after complexation of the vinyl end group with ß-cyclodextrin in water. Via radical ring-opening copolymerization of 5 and NiPAAm a graft copolymer 8 with a clouding point of 32 °C was synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Amphiphilic host molecules, such as cyclodextrins, featuring a hydrophilic outer shell and a hydrophobic cavity, can complexate with hydrophobic guests present in a thermoresponsive polymer, thereby increasing its hydrophilicity and T CP . Many examples have been reported on complexation of cyclodextrins with endgroup guest-functionalized thermoresponsive polymers, including PNIPAAm-azo dye [83], PNIPAAm-vinylcyclopropane [84], or poly(N,N-diethylacrylamide)-4-alkylphenol with methylated bCDs [85]. As expected, T CP variations were found to be dependent on the excess of cyclodextrin host added, and typically increased by less than 5 K, although a T CP increase of close to 10 K was observed in a tert-butyl phenyl-terminated poly(N,N-diethylacrylamide) (PDEAAm) thermoresponsive polymer in the presence of 2 equiv.…”
Section: Modulating Polymeric Architectures By Supramolecular Interacmentioning
confidence: 99%
“…Amphiphilic host molecules, such as cyclodextrins, featuring a hydrophilic outer shell and a hydrophobic cavity, can complexate with hydrophobic guests present in a thermoresponsive polymer, thereby increasing its hydrophilicity and T CP . Many examples have been reported on complexation of cyclodextrins with endgroup guest-functionalized thermoresponsive polymers, including PNIPAAm-azo dye [83], PNIPAAm-vinylcyclopropane [84], or poly(N,N-diethylacrylamide)-4-alkylphenol with methylated bCDs [85]. As expected, T CP variations were found to be dependent on the excess of cyclodextrin host added, and typically increased by less than 5 K, although a T CP increase of close to 10 K was observed in a tert-butyl phenyl-terminated poly(N,N-diethylacrylamide) (PDEAAm) thermoresponsive polymer in the presence of 2 equiv.…”
Section: Modulating Polymeric Architectures By Supramolecular Interacmentioning
confidence: 99%
“…33 The end-functionalization of thermoresponsive polymers with various hydrophobic guest molecules and the interaction of these hydrophobic end-groups with supramolecular hosts has been shown to be an effective way to alter polymer phase transition temperatures. [34][35][36] For example, β-cyclodextrin has been exploited to tune the LCST of end-functionalized PNIPAMs bearing a pyrenyl group by the selective complexation of hydrophobic chain ends, resulting, due to the masking effect of the hydrophilic host molecule, in an increase of the T CP of polymers. 37 Woisel and co-workers have shown that the LCST phase transition temperature of 1,5-dialkoxynaphthalene-terminated PNIPAM could be increased by ca.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the authors nicely demonstrated that the livingness of a RAFT process depends on the knowledge of polymerization kinetics. 24 The assembly of new polymeric structures by non-covalent interactions, such as hydrogen bonding, ligand-metal coordination or "host-guest" inclusion complexation, has recently attracted considerable interest. Interest in smart polymers has remained high over many decades, displaying great promise in numerous nanotechnological and biomedical applications.…”
Section: Introductionmentioning
confidence: 99%